Going to Jail Sucks (And It Really Doesn’t Matter Who You Ask) - May, David C. (American journal of criminal justice, 2014)
A growing body of research suggests that, according to both offenders and criminal justice practitioners, jails and correctional boot camps are viewed and experienced as significantly more punitive than prison. Nevertheless, limited research exists examining the perceptions of the public regarding jail conditions and operations. Using responses from 1,183 Kentucky adults, we examine public opinion regarding the punitiveness of jail when compared to prison. We determine that, with the exception of boot camp, respondents feel that jail is the most punitive noncapital sanction. Additionally, respondents who had been convicted of a felony at some point in their lives and respondents with lower household income indicated that they would serve significantly less time in jail to avoid prison than their counterparts if given the option. Implications for policy and future research are discussed.